2011
DOI: 10.17813/maiq.16.4.p2xurw087553p6ln
|View full text |Cite
|
Sign up to set email alerts
|

The Movement Society in Comparative Perspective

Abstract: Recent scholarship argues that citizens in advanced democracies are turning to protests as a means of voicing political preferences. Advocates of this perspective claim that individuals now live in a "movement society," where protest activity stands alongside more traditional forms of political participation. However, despite the theoretical advances associated with the movement society approach, comprehensive evaluations of the underlying claims are lacking. This study remedies the empirical gaps by assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
10
2
Order By: Relevance
“…To overcome those deficiencies, other researchers have used pooled cross-sectional data to examine changing participation trends in nations and across nations. Dodson (2011), for instance, among many others, investigated the emergence of the hypothesized social movement society in 18 democratic countries that are included in the World Values Survey from 1981 to 2008. He concluded that “the evidence indicates that citizens are highly involved in movement activities today—indeed, they are more involved today than at any point in the past 30 years” (p. 491).…”
Section: Studying Late Adolescents’ Willingness To Protestmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome those deficiencies, other researchers have used pooled cross-sectional data to examine changing participation trends in nations and across nations. Dodson (2011), for instance, among many others, investigated the emergence of the hypothesized social movement society in 18 democratic countries that are included in the World Values Survey from 1981 to 2008. He concluded that “the evidence indicates that citizens are highly involved in movement activities today—indeed, they are more involved today than at any point in the past 30 years” (p. 491).…”
Section: Studying Late Adolescents’ Willingness To Protestmentioning
confidence: 99%
“…As researchers observed that protest demonstrations, boycott, and petitioning became more widespread and increasingly legitimate channels of political participation across many advanced democracies since the 1970s (McCarthy, Rafail, and Gromis 2013; Meyer and Tarrow 1998; Soule and Earl 2005; Taylor 2000; see also Piven and Cloward 1992), the idea of a “social movement society” emerged. A social movement society is defined not only by a large volume of protest mobilization (Soule and Earl 2005) but also by citizens’ perceptions that protest is a normal and acceptable form of political voice leading to a widespread willingness to take part in protest (Caren, Ghoshal, and Ribas 2011; Dodson 2011). Despite the extensive research on adult protest participation, scholars have paid relatively little attention to late adolescents’ protest participation and willingness to protest (which we will call protest potential) and how they might have changed over time.…”
mentioning
confidence: 99%
“…They are less-planned and less-structured events, providing a different mobilizing context than ritual events. In some cases, reactive demonstrations take contentious and confrontational forms (Dodson 2011). Reactive protests involve relatively higher levels of risk and uncertainty, as less information is known beforehand on the likely unfolding of events and the outcome of the mobilization.…”
mentioning
confidence: 99%
“…From a disruption-oriented perspective, we consider this view to be both pessimistic and to rest upon an overly narrow conception of resistance as is often the case within CPE.Thus, in the 1960s and 1970s, we argue, the paradigmatic form of resistance was constituted by a circulation of struggles that questioned the social compromise acquired in much of Western and Northern Europe, as well as the exhaustion of the military and dictatorial regimes in much of Southern Europe. Labour militancy (in terms of strikes and other forms of industrial conflict) peaked during the 1970s, whilst participation in new social movements and other forms of extra-parliamentary, or (especially in Southern Europe) clandestine, activity continued to grow steadily throughout the post-war period(Crouch and Pizzorno 1978;Kriesi et al 1995;Dodson 2011). The rise in labour militancy during the 1960s and 1970s prompted a much-noted profit squeeze across Western Europe, alongside a subsequent drop in growth, as wages tended to increase in response to outbursts of industrial conflict(Paldam and Pedersen 1982;Glyn 2006).…”
mentioning
confidence: 99%